Spatial epidemiology of African swine fever: Host, landscape and anthropogenic drivers of disease occurrence in wild boar - Podgórski, Tomasz; Borowik, Tomasz; Łyjak, Magdalena; Woźniakowski, Grzegorz (Preventive veterinary medicine, 2020)
Host abundance and landscape structure often interact to shape spatial patterns of many wildlife diseases. Emergence, spread, and persistence of African swine fever (ASF) among wild boar in eastern Europe has raised questions on the factors underlying ASF dynamics in this novel host-pathogen system. This work identifies drivers of ASF occurrence in natural wild boar population. We evaluated factors shaping the probability of ASF-postitive wild boar during the first three years (2014-2016) of the ASF epidemic in Poland. We expected to observe positive effects of wild boar density, proportion of forested area, human activity, and proximity to previous infections on ASF case probability. We tested these predictions using the infection status of 830 wild boar samples and generalized mixed-effects models. The probability of ASF case increased from 3 to 20% as population density rose from 0.4 to 2 ind./km2. The positive effect of population density on ASF case probability was stronger at locations near previous ASF incidents. ASF was more likely to occur in forested areas, with the probability of detecting an ASF positive sample rising from 2 to 11% as forest cover around the sample increased from 0.5 to 100%. This pattern was consistent at both low and high wild boar densities. Indicators of human activity were poor predictors of ASF occurrence. Disease control efforts, such as culling and carcass search, should be focused on high-density populations where chances of detecting and eliminating ASF-positive wild boar are higher. The intensity of control measures should decrease with distance from the infected area to match the observed spatial pattern of ASF case probability. Woodlands represent areas of the highest risk of ASF case occurrence. Distribution and connectivity of suitable habitats over the landscape can be used to prioritize disease-management actions.
Keywords: Environment; Spatial Analysis; Animals; africký mor prasat; biologické modely; epidemie; Sus scrofa; divoká zvířata; Models, Biological; Probability; virus afrického moru prasat; prasata; African Swine Fever Virus; pravděpodobnost; Animals, Wild; Swine; Epidemics; interakce hostitele a patogenu; životní prostředí; African Swine Fever; zvířata; Host-Pathogen Interactions; Poland; prostorová analýza; Polsko